2020
DOI: 10.3389/fchem.2020.579891
|View full text |Cite
|
Sign up to set email alerts
|

Use of Natural Products in Leishmaniasis Chemotherapy: An Overview

Abstract: Leishmaniasis is an infectious parasitic disease that is caused by protozoa of the genus Leishmania, a member of the Trypanosomatidae family. Leishmaniasis is classified by the World Health Organization as a neglected tropical disease that is responsible for millions of deaths worldwide. Although there are many possible treatments for leishmaniasis, these treatments remain mostly ineffective, expensive, and long treatment, as well as causing side effects and leading to the development of resistance. For novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 96 publications
(127 reference statements)
0
42
0
1
Order By: Relevance
“…We observed that carajurin induced the depolarization of the mitochondrial membrane of the promastigote parasite, showing that this compound is capable of crossing the plasma membrane and causing a collapse of the mitochondrial membrane of the parasite. Several plant compounds that cause mitochondrial damage and parasite death have their mechanisms of action attributed mainly to the potential dysfunction of the mitochondrial membrane [ 20 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that carajurin induced the depolarization of the mitochondrial membrane of the promastigote parasite, showing that this compound is capable of crossing the plasma membrane and causing a collapse of the mitochondrial membrane of the parasite. Several plant compounds that cause mitochondrial damage and parasite death have their mechanisms of action attributed mainly to the potential dysfunction of the mitochondrial membrane [ 20 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Starting in the 1950s, pentavalent antimonial compounds were introduced as treatments against Leishmania species; however, these drugs are associated with several adverse events and are becoming increasingly ineffective due to the development of resistance [ 12 , 13 ]. Other drugs used to treat leishmaniasis include amphotericin B in a liposomal formulation, which significantly reduced the side effects and treatment duration associated with amphotericin B in the free form but is very expensive; and paromomycin and miltefosine, which are associated with high toxicity (particularly renal toxicity), increased resistance, and teratogenic and abortifacient effects [ 4 , 12 ]. Therefore, alternative chemotherapies must be developed to improve the control and elimination of this group of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products, with their enormous chemical diversity, are a major resource for the discovery and development of novel therapeutics ( Ioset, 2008 ; Ndjonka et al., 2013 ). For parasitic diseases, most of the drugs in use are derived from natural products, often carrying specific modifications to maximize effectiveness ( Gervazoni et al., 2020 ). (−)-Epigallocatechin 3- O -gallate (EGCG), the most abundant flavanol constituent of green tea ( Camellia sinensis (L.) Kuntze; Theaceae), is widely studied and has generated considerable interest as a biologically active compound with a wide range of potential therapeutic activities ( Khan and Mukhtar, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are natural products that have demonstrated significant antiprotozoal activities ( Tasdemir et al., 2006 ; Gervazoni et al., 2020 ). Within this chemotype, (-)-Epigallocatechin 3- O -gallate (EGCG), the most abundant flavonoid constituent of green tea, was recently demonstrated to display activity against different species of Leishmania , including visceral leishmaniasis species ( L. infantum ( Inacio et al., 2019 )).…”
Section: Introductionmentioning
confidence: 99%